Alexithymia and temporomandibular joint and facial pain in the general population. (14th December 2018) - Kindler, Stefan; Schwahn, Christian; Terock, Jan; Mksoud, Maria; Bernhardt, Olaf; Biffar, Reiner; Völzke, Henry; Metelmann, Hans Robert; Grabe, Hans Jörgen
Summary: Background: Associations of alexithymia with temporomandibular pain disorders (TMD), facial pain, head pain and migraine have been described, but the role of the different dimensions of alexithymia in pain development remained incompletely understood. Objectives: We sought to investigate the associations of alexithymia and its subfactors with signs of TMD and with facial pain, head pain and migraine in the general population. Methods: A total of 1494 subjects from the general population completed the Toronto Alexithymia Scale‐20 (TAS‐20) and underwent a clinical functional examination with palpation of the temporomandibular joint and masticatory muscles. Facial pain, migraine and head pain were defined by questionnaire. A set of logistic regression analyses was applied with adjustment for age, sex, education, number of traumatic events, depressive symptoms and anxiety. Results: Alexithymia was associated with TMD joint pain (Odds Ratio 2.63; 95% confidence interval 1.60‐4.32 for 61 TAS‐20 points vs the median of the TAS‐20 score) and with facial pain severity (Odds Ratio 3.22; 95% confidence interval 1.79‐5.79). Differential effects of the subfactors were discovered with difficulties in identifying feelings as main predictor for joint, facial, and head pain, and externally oriented thinking (EOT) as U‐shaped and strongest predictor for migraine. Conclusion: Alexithymia was moderately to strongly associated with signs and symptoms of TMD. These results should encourage dental practioners using the TAS‐20 in clinical practice, to screen TMD, facial or head pain patients for alexithymia and could also help treating alexithymic TMD, facial or head pain patients.